2016
DOI: 10.1590/0102-33062016abb0292
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and histochemistry of glandular trichomes in Hyptis villosa Pohl ex Benth. (Lamiaceae) and differential labeling of cytoskeletal elements

Abstract: Lamiaceae contains many species known for their aromatic properties that are produced by the production of essential oils in glandular trichomes. Hyptis is one of the most common genera of Lamiaceae in the Brazilian fl ora, and includes several species with medicinal value. However, studies on the morphology and functioning of their glandular trichomes are lacking. We analyzed the morphology, histochemistry and ultrastructure of the glandular trichomes in leaves of H. villosa, emphasizing the diff erential dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…D. moldavica leaves, stems, and flowers are covered by numerous glandular and non-glandular trichomes (Dmitruk and Weryszko-Chmielewska 2010), as in many other species from the family Lamiaceae (Ascensão et al 1995;Corsi and Bottega 1999;Chwil et al 2016;Janošević et al 2016;Haratym and Weryszko-Chmielewska 2017;Tozin and Rodrigues 2017). Previous studies of D. moldavica trichomes on the leaves conducted by other researchers with the use of the available methods, mainly LM, demonstrated different findings.…”
Section: Introductionmentioning
confidence: 99%
“…D. moldavica leaves, stems, and flowers are covered by numerous glandular and non-glandular trichomes (Dmitruk and Weryszko-Chmielewska 2010), as in many other species from the family Lamiaceae (Ascensão et al 1995;Corsi and Bottega 1999;Chwil et al 2016;Janošević et al 2016;Haratym and Weryszko-Chmielewska 2017;Tozin and Rodrigues 2017). Previous studies of D. moldavica trichomes on the leaves conducted by other researchers with the use of the available methods, mainly LM, demonstrated different findings.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis using transmission electron microscopy demonstrated that this denser aspect of the lens-shaped cell is likely due to the extensive ingrowths formed in the outer periclinal wall, in addition to the electron-dense cytoplasm. The occurrence of labyrinthine projections in cell walls has been reported for a variety of secretory structures (Bourett et al 1994;Gama et al 2016;Tozin & Rodrigues 2017), including hydropotes (Lüttge & Krapf 1969), and highlights the role of the cells bearing them in the transport of substances. Labyrinthine projections of walls increase the surface area of the plasma membrane supporting exchange among cells (Pate & Gunning 1972).…”
Section: Discussionmentioning
confidence: 93%
“…(Seyedi & Salmaki, ), Hyptis villosa Pohl ex Benth. (Tozin & Rodrigues, ), Salvia divinorum Epling & Játiva (Kowalczuk et al, ), S. nemorosa L. (Talebi et al, ) and L. dentata (Justus et al, ).…”
Section: Resultsmentioning
confidence: 99%